2023
DOI: 10.1088/1361-6463/ad039a
|View full text |Cite
|
Sign up to set email alerts
|

Review on high-performance bulk MgB2 superconductors

M Muralidhar,
Malik Shadab,
A Sai Srikanth
et al.

Abstract: Although the fascinating effect of superconductivity was discovered more than one hundred years ago, only a few low-temperature superconductors, especially Nb3Sn and NbTi, have reached everyday-life use. After the discovery of superconductivity in MgB2 in 2001, a boom appeared in interest in employing MgB2 in commercial applications, facilitated by simple crystallographic structure, high critical temperature, low-cost raw ingredients, simple and fast production, and other advantages for moderate temperature ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 179 publications
0
2
0
1
Order By: Relevance
“…Given that the superconductivity of MgB 2 has already undergone extensive theoretical and experimental examination, a detailed discussion is omitted here. For a more comprehensive understanding of its superconducting properties, please refer to [102,103].…”
Section: Mgb 2 Superconductormentioning
confidence: 99%
“…Given that the superconductivity of MgB 2 has already undergone extensive theoretical and experimental examination, a detailed discussion is omitted here. For a more comprehensive understanding of its superconducting properties, please refer to [102,103].…”
Section: Mgb 2 Superconductormentioning
confidence: 99%
“…Currently, MgB 2 wires made by the powder-in-tube (PIT) method are most often used in the construction and design of superconducting magnets for magnetic energy storage (SMES), wind turbines, magnetic resonance imaging (MRI), cables and electric motors [ 1 , 2 , 3 ]. This is due to the low anisotropy, inexpensive components, high critical temperature, high upper magnetic field, and low mass density of these materials [ 4 , 5 , 6 , 7 ]. These advantages are more important when the production of monocore or multi-filament PIT MgB 2 wires with lengths longer than 1 km is desired.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent progresses in bulk fabrication techniques has allowed for the manufacturing of MgB 2 bulks with high trapped field values even in small-sized samples [ 20 , 21 ]. It was reported that the critical current densities and trapped field depend on the density and homogeneity of the MgB 2 superconducting material and pinning centers [ 19 , 22 ]. Studies indicated that the homogeneity and density of the superconducting MgB 2 material and the density of pinning centers can be improved by thermal treatment under high isostatic pressure or by an increase of the density of the MgB 2 material before the synthesis reaction [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%